1978
DOI: 10.1104/pp.62.5.751
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Factors in Sweet Potato Root Which Agglutinate Germinated Spores of Ceratocystis fimbriata, Black Rot Fungus

Abstract: A factor which agglutinates the germinated spores of Ceratocystis fIunbriata was isolated from the sweet potato root. The factor is a glycoprotein with a molecular weight of 1.6 x 106 daltons and required divalent cations such as Ca2+, Mn2+, Ni2+, and Mg2 for activity. The activity of the factor was pH-dependent. The factor also agglutinated rabbit erythrocytes and is classified as a phytohemagglutinin or lectin. The factor agglutinated germinated spores of seven strains of C. fimbrista to almost the same degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Ion-exchange treatment of the crude root components results in a lower-molecular-weight fraction which agglutinates almost all pseudomonads examined, with only slight variations in efficacy. A similar phenomenon was observed for strains of the fungus Ceratocystis fimbriata in their agglutination reactions with crude and purified extracts of sweet potato roots (17). The authors demonstrated the presence of a factor(s) in the crude root extract which was able to suppress agglutination reactions of the spores differentially and which probably was lost during the purification procedure.…”
Section: Discussionsupporting
confidence: 72%
“…Ion-exchange treatment of the crude root components results in a lower-molecular-weight fraction which agglutinates almost all pseudomonads examined, with only slight variations in efficacy. A similar phenomenon was observed for strains of the fungus Ceratocystis fimbriata in their agglutination reactions with crude and purified extracts of sweet potato roots (17). The authors demonstrated the presence of a factor(s) in the crude root extract which was able to suppress agglutination reactions of the spores differentially and which probably was lost during the purification procedure.…”
Section: Discussionsupporting
confidence: 72%
“…The factor was not inactivated by pronase-treatment in contrast to the slight inactivation reported in preceding papers. 2 , 3) This discrepancy in the effect of pronasetreatment might be ascribed to the presence of contaminating protein in the specimen in the preceding work, of which the degradative products interfered with agglutination. Moreover, the factor treated with pronase showed the same behavior as that of the non-treated one on DEAE-Sephacel column chromatography.…”
mentioning
confidence: 98%